Procrastination: ways of prevention, means of overcoming (Actual Problems of Psychology in Educational Institutions, 2021)
The article presents the external and internal factorscontributing to the occurrence of the phenomenon of procrastination;the survey reveals the essence of the procrastination concept as acomplex phenomenon; its varieties and classifications; it is also shownthe main types of procrastination; and it is presented the list of testsmade by known researchers concerning problems of the general andacademic procrastination; the article analyzes the means of preventingprocrastination based on self-regulatory skills proposed by variousscientists; the study shows several newest effective methods of strugglingprocrastination processes; the paper clarifies the ways of prevention andmeans of overcoming in order to stop the processes of inhibition of thequalitative personal development.
Keywords: procrastination, procrastinator, procrastination prevention, perfectionism, active procrastination, passive procrastination